PREFERENSI GAYA BELAJAR MAHASISWA AKUNTANSI - Sulastri, Sri Pujiningsih, (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2010)
This study aims to find the differences between learning style preference in accounting students. Results of this research useful to determine teaching strategies, so it can support improvement of student learning. Based on the analysis of test results using ANOVA can be concluded that there is no difference in student learning styles accounting students. Learning style preferences of three groups of students is the same that is more like the learning style dependent. Keywords: Gaya Belajar, Strategi Mengajar.